A study on disruption to recovery in business school of India during COVID-19 using appreciative inquiry approach from a multi-stakeholder perspective. (10th January 2023) - Gupta, Jaya; Dash, Itilekha; Tiwari, Himanshi
Business schools need to revisit, reflect and re-align to the new normal. The paper makes an attempt to identify the measures for institutional continuity taken by a leading private business school of India. A multi-stakeholder analysis was used to understand the intricacies of 'trilemma' (Admission-Teaching & Learning-Placement) of business education. An Appreciative Inquiry (AI) approach was implemented in the study. A series of 'Brainstorming' sessions were held in the virtual mode involving participants from various stakeholder groups, woven around the 5D approach of Appreciative Inquiry. The study gives an insight to the apprehensions and concerns of the different stakeholders related to the 'trilemma'. The over-arching schema for successful mitigation strategies implementation has been proposed. Research on micro-level measures to reposition management education in the new normal is scarce. The study uncovers the challenges and redundancies due to the abrupt shift and details synergetic and dynamic interventions for their mitigation.